Study on Perceived Stress and Physical Stress associated with WFH during COVID 19 Pandemic - Suruchi Pandey; Anamika Pandey (Indian Journal of Forensic Medicine & Toxicology, 2021)
Covid 19 changed the rulesof way corporate worldfunctioned months back. Normal was no more normalfor the people, cities andcountries of the world.The future of work arrived and people were compelled toshift their offices at their home. Employees working in every industry adopted to this change whether it waseducation or banking or IT or services or any other.Present study investigates the stress and physicalhealth of the employees to adopted to this change and wereworking from home during the pandemic. The questionnaire was used to seek inputs from the participantson perception and feelings about work from home along with infrastructures issues at forefront, perceivedstress and physical stress. The collected data was analysed using SPSS. The study is based on primary dataand feedback collected from 228 professional working from home. Out of which there were 124 male and104 female respondents.The finding of the study is interesting revealing several aspects of work from home. Study revealedinfrastructure issues while working from home added to the stress levels, perception about work from homewas correlated to stress, female employees working from home found infrastructure more challenging thanmale counterparts.The study implies changes in policies to make work from home work in favour of employees and thereby foremployers. Organisations will have to adopt to newer ways of taking care of employee’s wellbeing.